The first year (2011) Implementation of New Projects - Ljubica Milosavljević (University of Belgrade, 2016)
The first year (2011) Implementation of Projects of Department of Ethnology and Anthropology Faculty of Philosophy University of Belgrade, financed by the Ministry of Culture, Information and Information Society RS